Perfil nutricional de idosos do município de Vitória nos anos de 2009 a 2012 por meio do sistema de vigilância alimentar e nutricional (SISVAN®) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2019)
Nutritional profile of elderly individuals living in VItória county from 2009 to 2012 based on the food and nutrition surveillance system (SISVAN®)